Effect of order of exercise on performance during a complex training session in rugby players - Deutsch, M.; Lloyd, R. (Journal of Sports Sciences, 2008)
In this study, we examined the acute effects of manipulating exercise order when combining countermovement jumps and loaded parallel squats in a complex training session, and the acute effects of countermovement jumps and loaded parallel squats on sprinting performance. Eight rugby players participated in five trials, including two that involved performing loaded parallel squats followed by countermovement jumps or vice versa in a randomized cross-over design. Peak rate of force development and peak force were measured during countermovement jumps and loaded parallel squats. Peak power, jump height, and duration of amortization phase were also determined during the countermovement jumps. Peak force during squatting was significantly greater in both cross-over treatments (loaded parallel squats-countermovement jumps and countermovement jumps-loaded parallel squats) compared with the control (P = 0.05), although no significant interaction effects were observed. Prior countermovement jumps resulted in slower 5-m split and overall 20-m sprint times compared with the control (countermovement jumps vs. control: 5-m split, 1.23 s, s=0.11 vs. 1.13 s, s=0.11; overall 20-m, 3.29 s, s=0.19 vs. 3.18 s, s=0.18; P < 0.05). It is possible to combine heavy resistance and plyometric exercises without detriment to training performance, but sprint training should be performed independently to minimize any potential interference from prior resistance training.